2005
DOI: 10.1007/s11214-005-1962-2
|View full text |Cite
|
Sign up to set email alerts
|

Radio Wave Emission from the Outer Planets Before Cassini

Abstract: We review observations and theories of radio wave emissions from the outer planets. These include radio emissions from the auroral regions and from the radiation belts, low-frequency electromagnetic emissions, and atmospheric lightning. For each of these emissions, we present in more details our knowledge of the Saturn counterpart, as well as expectations for Cassini. We summarize the capabilities of the radio instrument onboard Cassini, observations performed during the Jupiter flyby, and first (remote) obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…It is the most intense component of Saturn's low-frequency radio spectrum, covering the range between a few kHz and $1.3 MHz, with a maximum intensity between 100 and 400 kHz. Spectral structures such as arcs and bursts are visible in SKR dynamic spectra, although less organized than in the Jovian case (see reviews by Kurth and Zarka [2001] and Zarka and Kurth [2005]). Measured variations of the SKR polarization along the Voyager 1 and 2 flyby trajectories allowed Galopeau et al [1995] (hereafter G95) to constrain the northern and southern SKR source locations.…”
Section: Skr Source Location and Originmentioning
confidence: 99%
“…It is the most intense component of Saturn's low-frequency radio spectrum, covering the range between a few kHz and $1.3 MHz, with a maximum intensity between 100 and 400 kHz. Spectral structures such as arcs and bursts are visible in SKR dynamic spectra, although less organized than in the Jovian case (see reviews by Kurth and Zarka [2001] and Zarka and Kurth [2005]). Measured variations of the SKR polarization along the Voyager 1 and 2 flyby trajectories allowed Galopeau et al [1995] (hereafter G95) to constrain the northern and southern SKR source locations.…”
Section: Skr Source Location and Originmentioning
confidence: 99%
“…Subsequent observations revealed that all magnetized planets are radio sources (see review by Zarka and Kurth, 2005). Radio waves can travel far from their source region, carrying spectral signatures of the local conditions where they are generated.…”
mentioning
confidence: 99%
“…e.g. Treumann, 2006) for the electroncyclotron maser to work, is a perpendicular velocity gradient on the electron phase space distribution function and the presence of mildly relativistic electrons in resonance (known since the seminal work of Wu and Lee, 1979). Again, this latter point is crucial.…”
Section: Downward Current Region Electron Holesmentioning
confidence: 99%
“…e.g. Zarka and Kurth, 2005;Hess et al, 2009;Louarn et al, 2007;Mottez et al, 2010;Treumann et al, 2011b;Bykov and Treumann, 2011, and references therein). Radiation that would be generated outside the electron hole in the perpendicular velocity gradient between the hole and the fast accelerated beam or between the beam and the background distribution will not experience amplification.…”
Section: Amplificationmentioning
confidence: 99%
See 1 more Smart Citation